Pyrrolidinones derived from (S)-pyroglutamic acid. Part 2. Conformationally constrained kainoid analogues - Dyer, J; King, A; Keeling, S; Moloney, M (2000)
Novel conformationally constrained glutamate analogues are readily available from (S)-pyroglutamic acid using a bicyclic lactam as a synthetic template; diastereocontrolled modification of the pyrrolidine ring using a sequential conjugate addition-substitution strategy permits access to several kainoid analogues in a versatile strategy. The pyrrolidinone ring conformation appears to be controllable by the nature of remote substituents on the heterocyclic ring. © The Royal Society of Chemistry 2000.